(untitled) (Fiep Bulletin - online, 2013)
Heart failure (HF) is a complex clinical syndrome characterized by the inability of the heart to generate adequate cardiac output. For this, the National Institute for Clinical Excellence recommends that Cardiac Rehabilitation through physical exercise is safe and effective as a treatment for patients with HF. The objective of this review was to identify current evidence of the effects of physical exercise inserted into a rehabilitation program in patients with HF. This is a literature review in the electronic databases Medline, PubMed, Lilacs, and SciELO held in the period from 2009 to 2012. When evaluating 10 manuscripts, the results showed that physical exercise inserted within a Cardiac Rehabilitation Program increases functional capacity (FC), reduces hospital readmissions, and decreases mortality and morbidity of this patient population. Thereby HF patients can perform their daily activities with less difficulty, improve the socioeconomic relationship, thus providing them a better quality of life.